The Effect of Cycling to the Working Mood. (March 2017) - Zaky, M; Suherman, A; Subarjah, H; Umaran, U
Abstract: Cycling activity is considered to give positive effect to mood. However, there are still less empirical data that support the statement. Therefore, this research aims to get data and facts through the experiment of cycling activity effect to working mood. The research method is Ex-Post facto. The samples were taken from the members of Bike to work (B2W) Bandung with the range of age about 20 to above 60 years old. The instrument in this research is The Brunel Mood Scale (BRUMS). The research was conducted in Taman Cikapayang Bandung. The data analysis in this research is SPSS 22 with some tests such as: Test of Normality with Kolomogorov-Smirnov, Test of Homogeneity with Lavene Statistic, and Test of Independent Sample to observe the average score of sample group. The result of the research shows that the cycling group has different average score of mood compare to the average score of control group. In other words, it can be concluded that cycling activity gives positive effect to the working mood.